Sport as social policy: midnight football and the governing of society - Ekholm, David (Routledge critical perspectives on equality and social justice in sport and leisure, 2023)
"This book analyses the increasing use of sport in European and Western welfare states as a tool of social policy and its promotion as a solution to social problems. Drawing on cutting edge research into Midnight Football in Sweden and exploring other community sport programs including Midnight Basketball in the US, this book shines new light on broader social transformations regarding urban segregation and social exclusion, social policy and the governing of welfare and social policy. Midnight football is a sports-based intervention targeting social inclusion and crime prevention in young people aged 12 to 25 in Sweden. The book takes a close look at its organization, pedagogy and potential outcomes, drawing important conclusions for how sport can and should be used in social development. It also offers new perspectives on how sport and the lives of young people intersect with and shape broader shifts in welfare and social policy in Western states, shifts that are manifested in increased inequality, social polarization, and profound changes in urban geographies. This is fascinating reading for anybody with an interest in the relationships between sport and wider society, or in sport development, sport policy, social policy, public policy or youth and social work"--